Heteropoly acid-based supported ionic liquid-phase catalyst for the selective oxidation of alcohols - Bordoloi, Ankur; Sahoo, Suman; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a heteropolyacid, molybdovanadophosphoric acid, onto ionic liquid-modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high activity in the aerobic oxidation of primary and secondary alcohols to aldehydes and ketones, respectively. No overoxidation of the primary alcohols to carboxylic acids was observed. Secondary alcohols were chemoselectively oxidized to ketones in the presence of primary alcohol, hetero atom, and allyl groups. This catalyst could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Air as an oxidant; Mesoporous silica SBA-15; Molybdovanadophosphoric acid; Selective oxidation; Supported ionic liquid

Highly selective catalytic hydrogenation of arenes using rhodium nanoparticles supported on multiwalled carbon nanotubes - Kakade, Bhalchandra A.; Sahoo, Suman; Halligudi, Shivappa B.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2008)
Rhodium nanoparticles (RhNPs; 4.9 +/- 0.4 nm) supported on multiwalled carbon nanotubes (Rh/MWNT), prepared by simple microwave treatment, show a remarkable catalytic activity for arene hydrogenation with enhanced turnover numbers of similar to 10000; disubstituted arenes show selective conversion of thermodynamically less favorable cis products (>80%). A series of arenes have been tested using various Rh-based catalysts, and a comparison of the results with that of reported rhodium catalysts shows unique selectivity under mild conditions.